Case Report: A case of uterine embryonal rhabdomyosarcoma in adult female—navigating the complexities of the diagnostic journey - Li, Sijing; Zhou, Dongni; Zu, Qiao; Jia, Ying (Frontiers in Oncology, 2025)
Rhabdomyosarcoma (RMS) is a soft tissue sarcoma originating from primitive mesenchymal cells that exhibit varying degrees of skeletal muscle differentiation. Although RMS predominantly affects children and adolescents—representing one of the most common pediatric solid malignancies—it is exceptionally rare in adults, constituting less than 1% of adult cancers. Due to its embryonic mesenchymal origin, RMS can develop in virtually any organ. In adults, the most common sites are the trunk (27%) and limbs (26%), with the reproductive tract accounting for 17%. Current understanding of adult embryonal RMS primarily relies on case reports, as it is often misdiagnosed as other benign or malignant solid tumors. Here, we report a case of botryoid RMS of the uterine cervix in an adult woman. The diagnostic process was prolonged; after five visits and four biopsies, the diagnosis of rhabdomyosarcoma was finally confirmed. Based on pathological findings and imaging examinations, the clinical stage was determined to be T1N0M0 and Intergroup Rhabdomyosarcoma Study (IRS) IA. The patient was initially scheduled for surgery following neoadjuvant chemotherapy. However, after one cycle of chemotherapy, she experienced massive vaginal bleeding and prolapse of the cervical polypoid mass. Due to significant psychological distress, the patient declined further chemotherapy and insisted on proceeding with surgery. Subsequently, she underwent a robot-assisted laparoscopic radical hysterectomy, bilateral salpingo-oophorectomy, and pelvic lymph node dissection. A total of six cycles of the VA chemotherapy regimen were administered both pre- and postoperatively. Unfortunately, the 8-month postoperative follow-up results were unfavorable. Less than a year after surgery, contrast-enhanced pelvic MRI revealed enlarged pelvic lymph nodes, suggesting a possible recurrence. The purpose of this study was to report a case of embryonal rhabdomyosarcoma (ERMS) of the uterine cervix in an adult woman and to highlight the diagnostic and therapeutic challenges associated with this condition.